Facet dependence for solvent-modulated proton-coupled electron transfer in furfural acetalization on Pd nanostructures - Porwal, Govind; Dandekar, Pallavi; Gorai, Twinkle; Khan, Tuhin Suvra; Haider, M. Ali; Gupta, Shelaka; Vinod, C. P. (Chemical Engineering Journal, 2025)
Furfural dialkyl acetals prepared via acetalization reaction of furfural and alcohols are promising biofuels. Using defined experiments and density functional theory (DFT) simulations, the structure-dependent activity and selectivity for furfural acetalization reaction in the presence of alcohols (methanol, ethanol, propanol and butanol) as solvents was studied over well-defined supported Pd nanostructures (octahedra (111), cubes (100) and spheres (both (111) and (100)). Pd cubes supported over TiO2 in the presence of ethanol as a solvent (at 303 K and balloon pressure H-2) exhibited 78 % conversion and 100 % selectivity for furfural diethyl acetal product in a short time (similar to 180 min). In contrast, Pd octahedra (111) and Pd spheres showed low conversions (18 % and 6 %) at the same reaction conditions. Interestingly, when used as a solvent, methanol showed the highest conversion (90 %) and selectivity (100 %) for furfural acetalization over Pd cubes. DFT simulations provided mechanistic insight into the reactivity of the two different Pd facets (111) and (100) in the presence of alcohol molecules towards furfural acetalization reaction. A three-step reaction mechanism was proposed for furfural acetalization with alcohols: (i) alcohol hydroxyl-dehydrogenation (ii) hydrogenation of furfural carbonyl oxygen, and (iii) formation of hemiacetal product. For all three steps, Pd (100) exhibited low activation barriers (51.6, 26.7 and 76.2 kJ/mol) compared to Pd (111) surface (78.6, 35.8 and 92.2 kJ/mol) in the presence of ethanol. The activation barriers for the above steps were further reduced to 47.8, 23.9 and 64.6 kJ/mol on Pd (100) in the presence of methanol, explaining the experimental high reactivity aided by methanol. DFT calculations elucidated the role of the hydrogen bonding network between the solvent molecules and adsorbate, enabling proton-coupled electron transfer for accelerated reactions.
Keywords: Acetalization; DFT; facet-dependent reactivity; furfural; Furfural dialkyl acetals; solvent effect

Tunable, amine-functionalized porous silica catalyst for CO2 transformation into cyclic organic carbonates at atmospheric pressure - Gorai, Twinkle; Thanasekar, Chandragopal; Kumar, Pawan; Babu, Athira; Kurungot, Sreekumar; Vinod, C. P. (Chemistry-A European Journal, 2025)
A silica catalyst with characteristic features of broad pore size distribution, large pore width and tunable basic sites was synthesized by a one-step green co-condensation synthesis method analogous to SBA-15 synthesis. The surface chemical features of the above catalyst were explored by XPS, N-2 and CO2 adsorption and desorption experiments. The catalyst showed 90% conversion of styrene oxide (SO) with nearly complete selectivity toward styrene carbonate (SC) in 7 hours under a solvent-free condition at a temperature of 120 degrees C with the aid of co-catalyst tetrabutylammonium bromide (TBAB). Moreover, the catalyst demonstrates versatility with various epoxide substrates, providing valuable insights into the cycloaddition reaction under ambient pressure conditions involving carbon dioxide. The mechanistic details of the catalytic conversion were investigated by the in-situ DRIFT studies and reported here.
Keywords: CO2 fixation; cyclic organic carbonates; heterogeneous catalysis; in-situ FTIR